A revision of the genus Cistanche (Orobanchaceae) in Israel, and considerations for its taxonomic circumscription in the Middle East - Dar Ben-Natan; Chris Thorogood (PhytoKeys)
The genus Cistanche is the subject of considerable taxonomic confusion due to reduced morphology, poor preservation in herbaria, and misidentification. Here we re-examine the Cistanche of Israel, a region that falls within the broader Middle Eastern centre of diversity for the genus, but has been neglected from systematic attention. In our reconsideration we address taxonomic confusion in the region and confirm the presence of C. tubulosa and C. violacea, report for the first time the occurrence of C. laxiflora plus a separate entity we refer to as C. tinctoria, and describe a new species, C. mimii. We observe considerable phenotypic plasticity hitherto unreported, for example fruit valve number. Together, our findings suggest that species circumscription and diversity are still poorly understood and require careful examination in the field at a local scale. We provide a key for all Cistanche species in the region, along with an assessment of their ecology and conservation considerations. Finally, we consider our findings within the broader context systematics in this complicated genus.